Epidermoid Cyst of Orbit in a Newborn - Handan Canan; Rana Altan-Yaycioglu; Nebil Bal; Birgin Törer; Bilin Çetinkaya-Çakmak; Hande Gülcan (Case Reports in Ophthalmological Medicine)
A 3-day-old male newborn presented with a severe proptosis of the left eye leading to exposure keratopathy. He underwent debulking of the cyst and biopsy of the tumour and received the pathological diagnosis of epidermoid cyst of orbit. Clinicopathological features of this rare disease are discussed.